Elastomers three-dimensional biomodels proven to be a trustworthy representation of the angiotomographic images - André Giacomelli Leal; Leonardo Brancia Pagnan; Raphael Teruaki Kondo; José Aguiomar Foggiatto; Guilherme José Agnoletto; Ricardo Ramina (Arquivos de Neuro-Psiquiatria)
ABSTRACT Intracranial aneurysm (IA) rupture is responsible for 80% of spontaneous arachnoid hemorrhages and associated with an extremely high mortality rate. Two possible surgical interventions are endovascular embolization and microsurgical clipping. Three-dimensional (3D) prototyping models help in surgical planning minimizing perioperative risks in both methods and reducing operating time. Methods 3D biomodels were printed with flexible material (elastomer) using angiotomographic DICOM acquired images and compared to 3D digital subtraction angiography (DSA) images. Results 3D biomodels represented the aneurysm angioarchitecture exactly, especially the neck and domus features. Conclusion Elastomers 3D biomodels proved to be a trustworthy representation of the angiotomographic images and could be used to help surgical planning in IA treatment.